PENERAPAN METODE PEMBELAJARAN STEAM (SCIENCE, TECHNOLOGY, ENGINEERING, ART, AND MATHEMATICS PADA ANAK USIA 5-6 TAHUN di TKIT JUARA PADANG PANJANG - Wati, Kamal (PSGA LP2M IAIN Pontianak, 2024)
Abstrak: According to NAECY (National Association for the Education of Young Children), early childhood is in the age range 0-8 years which is covered in educational programs in child care, family child care home, pre- school education. both private and public schools, kindergartens and elementary schools. The growth and development of early childhood needs to be directed at balanced physical, cognitive, socio-emotional, creativity and language as an appropriate foundation for the formation of a complete person. The form of research that will be used in this study is a type of qualitative research. Qualitative research in which researchers conduct in-depth exploration of programs, events, processes, activities, for one or more people, means the process of exploring and understanding the meaning of individual and group behavior, describing social problems or humanitarian problems. The research method used in this study is descriptive analysis. The data analysis used is inductive based on facts found in the field and then constructed into hypotheses or theories. The object of the research is students at TKIT Juara Padang Panjang, this descriptive research aims to learn about the application of STEAM learning methods (science, technology, engineering, art, and mathematics) in children aged 5-6 years at TKIT Juara Padang Panjang. Data collection techniques are observation, interview, and document techniques. From the results of the study, it can be concluded that the application of the STEAM learning method in children aged 5-6 years at TKIT Juara Padang Panjang. From forming a small group after that, they started learning using technology such as watching stories that fit the theme using laptops, cellphones, and infocus, as well as using loose parts materials (natural materials such as: wood branches, leaves, sand, gravel, charcoal, grains and kitchen utensils used for cooking such as spoons, forks, cans and so on. Plastics such as cups, spoons, used bottles, clear plastic/crackles, straws and so on. Wood such as bamboo, beams and so on. The inhibiting factors are the lack of human resources, the creation of a design that takes a long time, the lack of training in STEAM learning methods and the supporting factors are the old awareness of the importance of learning from an early age, participation and good communication between teachers and parents.Keywords: STEAM Learning Method, Early Childhood Education